2021
DOI: 10.3390/ijms22020733
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA Methylation in Prostate Tumors from Puerto Rican Men

Abstract: In 2020, approximately 191,930 new prostate cancer (PCa) cases are estimated in the United States (US). Hispanic/Latinos (H/L) are the second largest racial/ethnic group in the US. This study aims to assess methylation patterns between aggressive and indolent PCa including DNA repair genes along with ancestry proportions. Prostate tumors classified as aggressive (n = 11) and indolent (n = 13) on the basis of the Gleason score were collected. Tumor and adjacent normal tissue were annotated on H&E (Haemotoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Puerto Rican Hispanic/Latino men are at an increased risk of prostate cancer-specific mortality compared with NHW men. However, the relationship between this observation and epigenetics and how this relationship explains PCa racial and ethnic health disparities are controversial [ 26 ]. This study represents an ongoing effort to investigate DNA methylation in PR H/L men with PCa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Puerto Rican Hispanic/Latino men are at an increased risk of prostate cancer-specific mortality compared with NHW men. However, the relationship between this observation and epigenetics and how this relationship explains PCa racial and ethnic health disparities are controversial [ 26 ]. This study represents an ongoing effort to investigate DNA methylation in PR H/L men with PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The first strength is that it is the largest study of epigenome-wide DNA methylation profiles of PR PCa patients. We previously reported results of epigenome-wide methylation analysis based on 24 PR PCa cases [ 26 ]. The second strength is that the identification of DNA methylation profiles associated with risk and aggressiveness of PCa in PR H/L men will provide a potential mechanism for studying PCa disparities in the PR population and to generate hypotheses for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC17A2 is a protein-coding gene that is perceived only in the membrane and cytoplasm of hepatocyte, as shown in the tissue distribution diagram. One study indicated signi cant differentially methylated CpG sites between aggressive and indolent prostate cancers, and SLC17A2 was hypomethylated [11], which illustrated that the methylation of SLC17A2 enhanced tumor invasiveness. In addition, SLC17A2 is involved in various metabolic pathways as a critical transcription factor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the expression of collagen gene COL5A3 plays an important role in bone formation 11 . Some studies have shown that COL5A3 is involved in the occurrence and development of a variety of tumors, including breast cancer 12 , uveal melanoma 13 , prostate cancer 14 , renal cell carcinoma 15 and so on. Although it has been reported that COL5A3 is highly expressed in many tumors by high-throughput sequencing, the correlation between the expression of COL5A3 in pancreatic cancer and its prognostic value has not been reported.…”
Section: Introductionmentioning
confidence: 99%